Psychosocial outcomes at 18 months after good neurological recovery from aneurysmal subarachnoid haemorrhage. Issue 8 (16th July 2004) - Powell, J; Kitchen, N; Heslin, J; Greenwood, R
Abstract : Objectives: To evaluate functioning, 18 months after surgery, of 49 patients with good neurological recovery following aneurysmal subarachnoid haemorrhage (SAH), and to determine the extent of any improvements in disturbances of mood, cognitive functioning, and levels of activity and participation previously observed at 9 month follow up. Methods: SAH patients, matched for age, gender, and occupation with healthy control participants, completely quantitative measures of mood (HADS, FIES, BDI) and activity/participation (BICRO-39 scales), and a brief cognitive assessment battery (verbal fluency, digit span, prose recall). Controls completed the HADS and the BICRO-39. Results: Patients showed some recovery of cognitive functioning, though impairments of prose recall persisted. Anxiety and depression symptoms were higher in patients than in controls, but fewer than 20% scored in the clinical range on any questionnaires except for RIES-Intrusive thoughts (22%); only three showed signs of full blown post-traumatic stress disorder. Almost half showed elevated dependence on others for domestic activities and organisation and abnormally low levels of employment. Very little variance in outcome was predicted by demographic variables, neurological or cognitive impairment, prior life stress, or mood. However, levels of social activity and self-organisation were related to persisting fatigue. Conclusions: The observed decline in intrusive thoughts and avoidance over time is consistent with that seen after life threatening illness or trauma. The persistent reductions in independence and levels of employment may in some cases reflect considered lifestyle adjustments rather than adverse and unwanted changes but in others indicate a need for focused rehabilitation.